Enteral nutrition for elderly patients in intensive care unit settings - Simone Dini; Mariagiovanna Cozza; Aurora Vitali; Francesca Flavia Rossi; Virginia Boccardi; Vincenzo Gianturco; Giulia Musatti (Geriatric Care, 2024)
Nutrition plays a fundamental role in the management of frail elderly patients. Indeed, effective management can reduce common pathological situations, such as malnutrition, refeeding syndrome, and aspiration pneumonia, which can increase morbidity and mortality in intensive care unit settings. To optimize this management, it is essential to have knowledge of basic aspects such as timing, route, and composition of nutrition, as well as the prevention and management of the most common adverse events.